Needs Assessment of Blended Learning Based Islamic Education on Higher Islamic Education Samarinda - Setiawan, Agus (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2020)
This research aims to determine the potential and needs of lecturers and students in PAI learning which will be applied with the blended learning strategy. This research is a descriptive research with triangulation method and data sources. Data was collected through preliminary observations, analysis of students condition got from survey results (google form online) to 21 students from 4 faculties and several study programs, and interviews (lecturers and students). As for the data analysis used by adopting models from Miles, Huberman and Saldana, namely with three steps: data reduction, data display and withdrawal of conclusion data. The results of the study state that the potential and needs based on need assessment at IAIN Samarinda are: 1) the blended learning model is indispensable for the current technological development conditions at IAIN Samarinda, and on the achievements of KKNI in implementing learning with ICT, 2) survey results through google online form states that the analysis of student needs for innovative and interesting learning is 100% and student opinions about the learning needs of blended learning at IAIN Samarinda is 81%. 3) the expectations of this assessment need are: a) the blended learning model should have been implemented at university by looking at technological developments, b) the need for a complete module on blended learning (including RPS, learning devices, e-learning and evaluation) so that the implementation can be achieved, c) pedagogical socialization of blended learning to lecturers and students, d) facilities and infrastructure, e) and policies regarding the implementation of blended learning.The implication of this research could be a reference for other researchers to develop blended learning model in higher education.